Numerical collocation technique for solving modified equal width wave equation - Aqib Zafar; Shyam Sundra Santra; Muhammad Nasir (Computational Algorithms and Numerical Dimensions)
In this article, Cubic Trigonometric B-Spline Collocation technique is used to solve Modified Equal Width (MEW) Wave equation with application. The proposed scheme of major equation is tested by three ways: Single Soliton Wave, train of Solitary Waves and final birth solution. The efficiency and validity i.e, of proposed method is checked by different time levels. The present scheme is implemented to find out three invariants quantities and two error  and  norms. The given scheme is stabled via Von Neumman method. The obtain results are improved from earlier results. Some examples are listed to show the effusiveness and validity of the main results.